Periodontal management in patients with diabetes: the impact of periodontal treatment on cardiometabolic biomarkers - Alicia Morales; Gustavo Sáenz-Ravello; Loreto Matamala; Mauricio Baeza; Patricia Hernández-Ríos (Frontiers in Oral Health, 2026)
Introduction Type II Diabetes Mellitus (T2DM) and periodontitis present an independent bidirectional relationship. While T2DM is associated with a higher prevalence, incidence, and severity of periodontitis, periodontitis might worsen glycemic control and inflammatory biomarker levels in diabetics. Although there is no standardized therapy for the treatment of diabetic patients with periodontitis, different periodontal interventions report improvements in clinical and cardiometabolic parameters. Objective To summarize the current evidence regarding the clinical management of patients with T2DM and periodontitis, with a secondary focus on the impact of periodontal interventions on cardiometabolic biomarkers. Materials and methods A literature search was conducted between 2010 and 2026. Information about the clinical management of periodontitis in individuals with T2DM and its impact on cardiometabolic biomarkers was classified and summarized. Results A comprehensive periodontal examination and diagnosis should be performed, with close collaboration with the patient's physician. Prior dental treatment, capillary blood glucose between 70 and 180 mg/dL, and up to 240 mg/dL in emergency procedures are suggested. The EFP's stepwise treatment approach is recommended, considering periodontal therapy in multiple sessions. Antibiotic therapy or prophylaxis are not recommended in all cases, whereas periodontal maintenance may be required every 3–6 months. Periodontal interventions in diabetic individuals have been shown to decrease glycated hemoglobin (HbA1c) and C-reactive protein (CRP), together with other inflammatory and cardiometabolic biomarkers. Conclusions Patients with T2DM benefit from several periodontal treatment strategies, with a positive impact on inflammatory and cardiometabolic biomarkers associated with eventual reductions in diabetic control and systemic inflammation.